Sensitivity analysis of traffic congestion costs in a network under a charging policy. Issue 1 (March 2015) - Mussone, Lorenzo; Grant-Muller, Susan; Laird, James
Highlights The paper proposes an analysis of Area C in Milan, Italy, where a charging policy is applied to private vehicles. A large number of scenarios with differing demand levels and elasticities by vehicle classes were explored. Further data collection included a parallel field survey of changes in PT speed was also undertaken. A high degree of correlation between changes in the different measures of congestion and changes in vehicle speed is observed. Changes in the total cost of congestion are though more marked than changes in the excess burden of congestion.